2006
DOI: 10.1079/pns2005474
|View full text |Cite
|
Sign up to set email alerts
|

Zinc: the missing link in combating micronutrient malnutrition in developing countries

Abstract: The first cases of human Zn deficiency were described in the 1960s in the Middle East. Nevertheless, it was not until 2002 that Zn deficiency was included as a major risk factor in the global burden of disease, and only in 2004 did WHO/UNICEF include Zn supplements in the treatment of acute diarrhoea. Despite this recognition Zn is still not included in the UN micronutrient priority list, an omission that will continue to hinder efforts to reduce child and maternal mortality, combat HIV/AIDS, malaria and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
186
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(199 citation statements)
references
References 92 publications
(106 reference statements)
3
186
0
10
Order By: Relevance
“…We evaluated three measures of growth that reflect subtle differences in nutritional status. Decreased length for age is associated with longer term energy deficits and/or specific nutrient deficiencies (e.g., zinc or iron (Gibson, 2006;Bougle, Laroche, & Bureau, 2000), while lower weight for age reflects recent deficits in energy intake. Head circumference is less susceptible to nutritional insult and more directly reflects brain growth (Black, 2003;World Health Organization, 1986).…”
Section: Aims Of the Current Researchmentioning
confidence: 99%
“…We evaluated three measures of growth that reflect subtle differences in nutritional status. Decreased length for age is associated with longer term energy deficits and/or specific nutrient deficiencies (e.g., zinc or iron (Gibson, 2006;Bougle, Laroche, & Bureau, 2000), while lower weight for age reflects recent deficits in energy intake. Head circumference is less susceptible to nutritional insult and more directly reflects brain growth (Black, 2003;World Health Organization, 1986).…”
Section: Aims Of the Current Researchmentioning
confidence: 99%
“…Back Cross) growing areas leads to inherently low grain Zn concentration and is considered as a major factor in low human Zn intake (Alloway 2009). Biofortification of staple food plants is considered a promising strategy to improve the Zn status (Gibson 2006). Biofortification is the increase of bioavailable nutrient density in edible crop plant parts through genetic or agronomic techniques (Cakmak 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that although there was a decrease in mineral content with extraction rate in all three varieties, the biofortified varieties maintained their substantially higher iron and zinc contents down to at least a 70% extraction rate (probably the maximum used in practice) (Hama et al, 2012). With zinc, the phytate: zinc ratio was much lower for the biofortified varieties (<18:1) than the traditional variety at all extraction levels, a ratio that corresponds to moderate bioavailability (Gibson, 2006). The phytate: ratio for iron of the biofortified varieties, although lower, was, however, considerably >1, indicating no improvement in iron bioavailability.…”
Section: Concerning Sorghum Cultivation Trials Of 29 Accessions In Tmentioning
confidence: 98%
“…Buckwheat has a total phenolic content ranging from 29 to 1371 mg/100 g, depending on the method of extraction, and which standard (gallic acid or ferulic acid) was used calibration Gallardo et al (2006); Guo et al (2011) Gallardo et al (2006( ) Przybylski et al (1998 Pasko et al (2008) concentrations, these have beneficial effects on cellular responses and immune function (Pham-Huy et al, 2008). However, at high concentrations they cause the condition known as oxidative stress which is harmful to cell structures.…”
Section: Introductionmentioning
confidence: 99%